Disentangling income inequality and the redistributive effect of taxes and transfers in 20 LIS countries over time - Koen Caminada; Kees Goudswaard; Chen Wang (Luxembourg Income Study (LIS), 2012)
In most OECD countries the gap between rich and poor has widened over the past decades. This paper analyzes whether and to what extent taxes and social transfers have contributed to this trend. Has the redistributive power of different social programs changed over time? The paper contributes to the literature by disentangling several parts of fiscal redistribution in a comparative setting. We use micro-data from the Luxembourg Income Study to examine household market inequality, redistribution from transfers and taxes, and the underlying social programs that drive the changes, for 20 countries from the mid-1980s to mid-2000s. The contribution of each program is estimated using a sequential accounting budget incidence decomposition technique. The aim of this paper is to offer detailed information on the redistributive impact of social transfer programs. We focus on changes in fiscal redistribution of 13 different social programs and taxes. We observe a sizeable increase in primary household inequality in all 20 countries over the last 25 years (except Ireland). In most countries, the extent of redistribution has increased too. Tax-benefit systems have offset two-third of the average increase in primary income inequality, although they appear to have become less effective in doing so since the mid-1990s. We find that the public old age pensions and the survivors scheme attribute 60 percent to the increase of redistribution during the period 1985-2005 for a subset of countries considered (with full tax/benefit information). Social assistance accounts for 20 percent, and the benefits for sickness, disease, and disability account for around 13 percent of the total increase in redistribution. Other transfers (invalid career benefits, education benefits, child care cash benefits and other child and family benefits) account for 22 percent of the total increase in redistribution. On the contrary, taxes slowed down redistribution by 17 percent during 1985-2005.
Keywords: H53; H55; I32; 330; welfare states; social income transfers; inequality; Gini coefficient; LIS; Steuerpolitik; Sozialpolitik; Wirkungsanalyse; Einkommensverteilung; Europa; USA